2013
DOI: 10.1016/j.jep.2013.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of Cymbopogon citratus leaves infusion via proteasome and nuclear factor-κB pathway inhibition: Contribution of chlorogenic acid

Abstract: inflammatory activity of Cymbopogon citratus leaves infusion via proteasome and nuclear factor-κB pathway inhibition: contribution of chlorogenic acid, Journal of Ethnopharmacology, http://dx.doi.org/10. 1016/j.jep.2013.03.077 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(46 citation statements)
references
References 26 publications
2
40
0
4
Order By: Relevance
“…For instance, the anti-inflammatory effect of an extract from Cymbopogon citratus (CC) in human macrophages was demonstrated. The results showed that the leaf extract of CC inhibits LPS-induced cytokine expression through NF-κB pathway [30]. In addition, Artemisia annua extract was applied on Caco-2 cells in order to reduce intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the anti-inflammatory effect of an extract from Cymbopogon citratus (CC) in human macrophages was demonstrated. The results showed that the leaf extract of CC inhibits LPS-induced cytokine expression through NF-κB pathway [30]. In addition, Artemisia annua extract was applied on Caco-2 cells in order to reduce intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Cymbopogon citratus (also known as lemongrass) leaves' infusion has been used in folk medicine of many tropical and subtropical regions to treat gastric disturbances and inflammatory conditions (Sagradas et al, 2015). Francisco et al (2013) showed the anti-inflammatory properties of C. citratus through proteasome inhibition and consequently NF-κB pathway and cytokine expression with Cy polyphenols, in particular chlorogenic acid as a bioactive compound. Francisco et al (2013) showed the anti-inflammatory properties of C. citratus through proteasome inhibition and consequently NF-κB pathway and cytokine expression with Cy polyphenols, in particular chlorogenic acid as a bioactive compound.…”
Section: Introductionmentioning
confidence: 99%
“…It is also recommended in folk medicine to treat gastric disturbances, stomachache, gastritis and ulcers (De Albuquerque et al, 2007;Novais et al, 2004;Tene et al, 2007). Studies on C. citratus leaves infusions and decoctions have shown antioxidant and anti-inflammatory activities (Carbajal et al, 1989;Cheel et al, 2005;Figueirinha et al, 2010Figueirinha et al, , 2008Francisco et al, 2013Francisco et al, , 2011Habana, 2001;Pereira et al, 2009) and revealed the presence of several polyphenols, including tannins, phenolic acids and flavonoids (Cheel et al, 2005;Figueirinha et al, 2008;Francisco et al, 2014;Marques and Farah, 2009;Pereira et al, 2009). Those properties may be indicative of the potential benefit in the gastrointestinal tract, mainly on gastric mucosal injury generated by oxidative damage.…”
Section: Introductionmentioning
confidence: 99%